Nevus-Like Appearance of Primary Malignant Melanoma of the Esophagus - Kang, Min-Jung (Hindawi Publishing Corporation, 2009)
The primary malignant melanoma of the esophagus (PMME) is a rare malignant disease, accounting for only 0.1–0.2% of all esophageal neoplasms, and the majority of the patients are diagnosed at advanced stages with poor prognosis. We present here a case of 56-year-old woman with epigastric pain and her endoscopic finding revealed several flat and black pigmented mucosal lesions within the distal portion of the esophagus which looked like flat nevus. The histopathology and immunohistochemical profile of the tissue specimens were diagnostic of malignant melanoma.